Mechanical Properties of Particle board from Empty Palm Fruit with Polyester Resin Adhesive - Istianto Budhi Rahardja; Hayya Afifah; Yudi Dermawan; Ery Diniardi; Anwar Ilmar Ramadhan; Januar Parlaungan Siregar (Journal of Applied Sciences and Advanced Technology, 2021)
The need for particleboard in Indonesia is increasing every year. Particleboard is usually made of wood that comes from the forest so it has a bad effect and forest products will decrease over time. To overcome this problem, new knowledge is created that can be done. The new knowledge is like utilizing empty palm oil bunches for particle board material to replace wood raw materials. Particleboard is usually made of wood or other lignocellulosic materials such as oil palm empty bunches. The empty fruit bunches that have been made will be mixed with polyester resin as an adhesive. This study examines the effect of the percentage of polyester resin adhesive used, namely 90%, 75% and 60%. The process of making particle board starts with the preparation of raw materials such as palm empty fruit bunches and polyester resin. For empty bunches fiber used is 1 cm long. After the particle board is made, a hardness test is carried out using a durometer with the ASTM D2240 standard.